Effectiveness of exercise for osteosarcopenia in older adults: a systematic review protocol. Issue 7 (2nd July 2021) - Vinícius-Souza, Guilherme Elias; Noll, Matias; Silveira, Erika Aparecida
Abstract : Introduction: Osteosarcopenia is defined as the concomitant occurrence of sarcopenia and osteopenia or osteoporosis. Older adults with this syndrome have a greater fragility and mortality risk compared with those without these conditions. Based on separate interventions with individuals with sarcopenia and osteoporosis, exercise has been recommended as a treatment for osteosarcopenia. However, there is no evidence of its efficacy. Our objective is to identify whether physical exercise can improve osteosarcopenia in older adults and lead to good health outcomes. Methods and analysis: We will perform a systematic review in the following databases: PubMed, Embase, Cochrane and Scopus. The criterion of inclusion will be clinical trials involving physical exercise interventions in older adults diagnosed with osteosarcopenia. To assess the risk of bias, the Grading of Recommendations, Assessment, Development and Evaluation and Downs and Black tools will be used. For each search result, the quality of the evidence will ultimately receive one of four grades: high, moderate, low or very low. The outcome of this study is to demonstrate the effectiveness of physical exercise in improving the parameters that lead to the diagnosis of osteosarcopenia (bone mineral density, quality of muscle mass, muscle strength and physical function) in older adults. The possibility of meta-analysis will be assessed according to the homogeneity of the studies, using the methods of fixed or random effects. Sensitivity analyses will be performed, and the funnel plot will be used to assess publication bias. The proposed statistical analyses will be performed using STATA software, V.14.0. Ethics and dissemination: The results of the systematic review will be disseminated via publication in a peer-reviewed journal and presented at a relevant conference. As we will not use individual patient data, ethical approval is not required. Trial registration number: CRD42020215659.